2012
DOI: 10.1007/s00436-012-3182-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of protective activities of Neospora caninum bradyzoite antigens, NcBAG1, NcBSR4, NcMAG1, and NcSAG4, in a mouse model of acute parasitic infection

Abstract: Neospora caninum is an obligate intracellular protozoan parasite that causes severe neuromuscular diseases, repeated abortion, stillbirth, and congenital infection in livestock and companion animals. The development of an effective vaccine against neosporosis in cattle is an important issue due to the significant worldwide economic impact of this disease. We evaluated the immunogenicity of four bradyzoite antigens, NcBAG1 (first described in this study), NcBSR4, NcMAG1, and NcSAG4, using an acute infection mou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 55 publications
0
11
0
2
Order By: Relevance
“…These results could be explained by means of the immunodominant role of NcGRA7, as mentioned above, or by a lower stimulation of the immune cells in those groups immunized with in rhoptry proteins due to a lower number of replicating parasites. Nevertheless, several vaccine trials employing rNcSRS2 (Haldorson et al, 2005;Pinitkiatisakul et al, 2005Pinitkiatisakul et al, , 2007, rNcPDI (Debache et al, 2010, rNcMIC3 (Cannas et al, 2003b), rNcROP2 (Debache et al, 2008(Debache et al, , 2010, chimeric protein rNcMIC3-MIC1-ROP2 and bradyzoite proteins (rNcBAG1, rNcMAG1 and rNcSAG4; Uchida et al, 2013) have evidenced the ability of these antigens to reduce the cerebral parasite load in infected mice. However, in terms of parasite burden, our results remained consistent with our previous studies (AguadoMartínez et al, 2009;Jiménez-Ruiz et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results could be explained by means of the immunodominant role of NcGRA7, as mentioned above, or by a lower stimulation of the immune cells in those groups immunized with in rhoptry proteins due to a lower number of replicating parasites. Nevertheless, several vaccine trials employing rNcSRS2 (Haldorson et al, 2005;Pinitkiatisakul et al, 2005Pinitkiatisakul et al, , 2007, rNcPDI (Debache et al, 2010, rNcMIC3 (Cannas et al, 2003b), rNcROP2 (Debache et al, 2008(Debache et al, , 2010, chimeric protein rNcMIC3-MIC1-ROP2 and bradyzoite proteins (rNcBAG1, rNcMAG1 and rNcSAG4; Uchida et al, 2013) have evidenced the ability of these antigens to reduce the cerebral parasite load in infected mice. However, in terms of parasite burden, our results remained consistent with our previous studies (AguadoMartínez et al, 2009;Jiménez-Ruiz et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, proteins located in micronemes, rhoptries and dense granules, organelles whose contents are involved in tachyzoite host cell adhesion and invasion, have emerged as promising vaccine targets to block parasite dissemination and foetal transmission during the acute phase of infection . Vaccine candidates have been traditionally selected based on their immunogenic capacities (Ellis et al, 2008), their role in tachyzoite to bradyzoite stage conversion (Aguado-Martínez et al, 2009;Jiménez-Ruiz et al, 2012;Uchida et al, 2013) and their implication in adhesion or invasion processes (Debache et al, 2009;Monney et al, 2011), with variable results in experimental mouse models. Recently, proteome expression changes in different isolates revealed that the rhoptry protein NcROP40 and the dense granule protein NcNTPase are more abundantly expressed in virulent isolates compared to isolates of low virulence (Regidor-Cerrillo et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneous immunization with recombinant antigens of N. caninum with DNA vaccines possessing the antigen genes of N. caninum may enhance the induction of immune responses to N. caninum in mice (18,26). In addition, the Th1 immune response can be induced by an oil-in-water emulsion with bitter ground extract (28).…”
Section: Expression Of Ncsag1 Ncsrs2 and Ncmic3 In Silkworm Larvae Amentioning
confidence: 99%
“…Other bradyzoite stage proteins in the known candidate list are MAG1 (a similar antigen to NcGRA1, NcGRA2, and NcGRA7 (Uchida et al, 2013) and SAG4. Both these antigens were predicted to be exposed with appropriate peptide-MHC binders.…”
Section: Ranking Of Vaccine Candidatesmentioning
confidence: 99%
“…Ortholog countnumber of orthologous genes as obtained from OrthoMCL DB version 5. (Uchida et al, 2013) Abbreviations: -= unknown; Ribi = Ribi Adjuvant System; FIA = Freund's incomplete adjuvants; VT = vertical transmission. a Vaccine candidates are from studies over the past 10 years that attempt to prevent infection, abortion or vertical transmission; b MIC1, MIC3, GRA2, GRA6 and SRS2 antigens were expressed in Brucella abortus strain RB51; c Four recombinant proteins of N. caninum (GRA1, GRA2, MIC10, and p24B), MIC10 and p24B provide best protection; d Protection = measured or described protection towards type of challenge, e UniProt F0VIH4 is an SRS domain-containing protein (Putative srs29b) but is not a complete sequence; f GRA6 sequence is 100% similar to GRA2; P24B is a possible novel protein; g Same protein as descrived in publication.…”
Section: Tablementioning
confidence: 99%